2013
DOI: 10.1002/cpp.1839
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Coping with Emotion in Schizophrenia: Acceptability, Feasibility and Case Illustrations

Abstract: Although current treatments help to alleviate some of the symptoms of schizophrenia, people with schizophrenia often continue to experience residual symptoms. An emotion-focused treatment approach may help to improve well-being in this population by increasing positive experiences and resources. In this article, we discuss the feasibility and acceptability of a skills-based group treatment for people schizophrenia or schizoaffective disorder. As part of the Awareness and Coping with Emotion in Schizophrenia (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Compared with programmes that combine SST with cognitive behavioural therapy (i.e., Granholm et al, ), MOSST aims to (a) train the metacognitive function and not to change dysfunctional thoughts. Disputing dysfunctional thoughts may be very difficult and sometimes counterproductive in patients with a predisposition to delusional beliefs; (b) train individuals' awareness of their own states (i.e., Caponigro et al, ) in order to give them more access to their wishes and needs and therefore engage themselves in meaningful goal‐directed social action; and (c) train both the therapist and the ‘metacognitive facilitators’ to show in vivo their mental functioning through self‐disclosures while giving feedback to patients. This is based on the evidence that difficulties in metacognition are partially dependent on problems in the intersubjective domain (Salvatore et al, , ; Stanghellini and Lysaker, ) and not just an ability that can be taught.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with programmes that combine SST with cognitive behavioural therapy (i.e., Granholm et al, ), MOSST aims to (a) train the metacognitive function and not to change dysfunctional thoughts. Disputing dysfunctional thoughts may be very difficult and sometimes counterproductive in patients with a predisposition to delusional beliefs; (b) train individuals' awareness of their own states (i.e., Caponigro et al, ) in order to give them more access to their wishes and needs and therefore engage themselves in meaningful goal‐directed social action; and (c) train both the therapist and the ‘metacognitive facilitators’ to show in vivo their mental functioning through self‐disclosures while giving feedback to patients. This is based on the evidence that difficulties in metacognition are partially dependent on problems in the intersubjective domain (Salvatore et al, , ; Stanghellini and Lysaker, ) and not just an ability that can be taught.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have begun to demonstrate the efficacy of interventions that specifically target positive affect for people living with chronic physical and mental health conditions (Boutin-Foster et al, 2016; Caponigro et al, 2013; Carrico et al, 2015; Cohn et al, 2014; Huffman et al, 2015; Huffman et al, 2011; Krentzman et al, 2015; Ogedegbe et al, 2012; Peterson et al, 2012; Seligman et al, 2005). Although most of these studies have been small pilot feasibility and preliminary efficacy studies, Charlson and colleagues have conducted larger-scale randomized trials of a positive affect intervention in samples of people with chronic illness and hypothesized that the intervention would have beneficial effects on health behaviors (Mancuso et al, 2012; Ogedegbe et al, 2012; Peterson et al, 2012).…”
mentioning
confidence: 99%
“…Sin and Lyubomirsky (2009) conducted a meta-analysis of 49 positive psychology interventions, and found that they were highly effective in enhancing positive mood and overall well-being, with a medium effect size of.29. Additionally, such positive psychology interventions enhance mood and well-being not only in healthy participants, but also in a range of patient populations, including those suffering from depression, anxiety, schizophrenia and HIV (Fava et al, 2005; Seligman et al, 2006; Moskowitz et al, 2012; Meyer et al, 2012; Caponigro et al, 2013). While the cognitive and underlying neural effects of these interventions are not yet known, this represents a fruitful area of future investigation.…”
Section: Behavioral Interventions Can Be Used To Improve Positive Moomentioning
confidence: 99%